Four Approaches to Subjective Experience from the Hermeneutic Phenomenological Research Methodology - Pacheco Pacheco, Cristóbal (2022)
In the present article an approach to the central approaches to the hermeneutic phenomenological methodology, as a way of approaching the particular subjective experience, is made. It is on the basis of philosophers such as Husserl (2012), Heidegger (2008) and Merleau-Ponty (1945), that possibilities of approaching the construction of reality at a particular level have arisen, which is an interesting field of study. This study makes a systematic review of 4 ways of approaching the particular experience from a phenomenological and hermeneutic dimension, the methodologies considered are: The human sciences paradigm for phenomenological study by Max Van Manen (1990); Descriptive phenomenological method in psychology by Amedeo Giorgi (1986, 2009); Microphenomenological interview by Claire Petitmengin (2006) and The Interpretative Phenomenological Analysis (IPA) by Jonathan Smith and Mike Osborn (2003).  As conclusions of the present study, we visualize the need to achieve a greater methodological structuring that at the same time respects the tradition of an unprejudiced approach to the study of phenomena, typical of phenomenology and hermeneutics.